World’s First 24/7 Mobile Stroke Unit: Initial 6-Month Experience at Mercy Health in Toledo, Ohio - Lin, Eugene; Calderon, Victoria; Goins-Whitmore, Julie; Bansal, Vibhav; Zaidat, Osama (Frontiers in Neurology, 2018)
Background and Purpose –As the fourth Mobile Stroke Unit (MSU) in the nation, and the first 24/7 unit worldwide, we review our initial experience with the Mercy Life Flight Network Mobile Stroke Unit and institutional protocols implemented to facilitate rapid treatment of acute stroke patients and field triage for patients suffering other time-sensitive acute neurologic emergencies in Lucas County, Ohio, and the greater Toledo metropolitan area. Methods – Data was prospectively collected for all patients transported and treated by the MSU for the first six months. Data was abstracted from documentation of on-scene emergency medical services (EMS) personnel, critical care nurses, and onboard physicians, who participated through telemedicine. Results – The MSU was dispatched 248 times and transported 105 patients after on-scene examination with imaging. Intravenous (IV) tPA was administered to 10 patients; eight patients underwent successful endovascular therapy after a large vessel occlusion (LVO) was identified on plain CT performed within the MSU without post treatment symptomatic hemorrhage. Moreover, 14 patients were treated with (IV) anti-epileptics for status epilepticus and 19 patients received (IV) anti-hypertensive agents for malignant hypertension. MSU alarm to on-scene times and treatment times were 34.7 minutes (25-49) and 50.6 minutes (44.4-56.8), respectively. Conclusions – The world’s first 24/7 MSU has been successfully implemented with IV tPA administration rates and times comparable to other MSU’s nation-wide, while demonstrating rapid triage and treatment in the field for neurologic emergencies including status epilepticus. With the rising number of MSU world-wide, further data will drive standardized protocols that can be adopted by EMS nation-wide.